2008
DOI: 10.1507/endocrj.k07-078
|View full text |Cite
|
Sign up to set email alerts
|

Association between Baseline Values of Bone Turnover Markers and Bone Mineral Density and Their Response to Raloxifene Treatment in Japanese Postmenopausal Women with Osteoporosis

Abstract: Abstract. It has been well established that raloxifene improves bone turnover, increases bone mineral density (BMD), and reduces the risk of fractures. However, it remains obscure which patients are more likely to respond to treatment with raloxifene in patients with postmenopausal osteoporosis. The purpose of this study was to investigate associations between baseline values of BMD and bone turnover markers (BTMs) and changes of those values after 1-year treatment with raloxifene. Sixty-eight Japanese postmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…When analyzing the data of bone metabolism, it is necessary to pay attention to the time at which the sample was taken from each individual and the turnover of bone metabolism, as differences in these factors may induce unexpected results. A previous study indicated that the rate of suppression of bone absorption markers by the administration of alendronate sodium hydrate was higher in patients with pretherapeutically accelerated turnover of bone metabolism [31] . In this study, we did not analyze the data according to the turnover of bone metabolism in each patient as the number of patients was small.…”
Section: Discussionmentioning
confidence: 96%
“…When analyzing the data of bone metabolism, it is necessary to pay attention to the time at which the sample was taken from each individual and the turnover of bone metabolism, as differences in these factors may induce unexpected results. A previous study indicated that the rate of suppression of bone absorption markers by the administration of alendronate sodium hydrate was higher in patients with pretherapeutically accelerated turnover of bone metabolism [31] . In this study, we did not analyze the data according to the turnover of bone metabolism in each patient as the number of patients was small.…”
Section: Discussionmentioning
confidence: 96%